2017
DOI: 10.18632/oncotarget.17117
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PEPT1: a novel strategy to improve the antitumor efficacy of doxorubicin in human hepatocellular carcinoma therapy

Abstract: Proton coupled oligopeptide transporter 1 (PEPT1) is a member of the peptide transporter superfamily and plays important role in the absorption of oligopeptide and peptidomimetic drugs. Our previous research verified that PEPT1 expressed specifically in human Hepatocellular carcinoma (HCC) tissue and cell lines and showed potential transport activity to be a new candidate of the tumor therapeutic target. In this study, we aim to explore the feasibility of a novel tumor target therapeutic strategy: Targeting PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…This overlapping indicated that the mutation in rs2297322 was crucial in occurrence of docetaxel‐induced myelosuppression. SLC15A1 codes for Peptide transporter 1 (PepT‐1) and is responsible for absorption of small peptides . It plays an important role in the metabolism of oligopeptide and peptidomimetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This overlapping indicated that the mutation in rs2297322 was crucial in occurrence of docetaxel‐induced myelosuppression. SLC15A1 codes for Peptide transporter 1 (PepT‐1) and is responsible for absorption of small peptides . It plays an important role in the metabolism of oligopeptide and peptidomimetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, POT-mediated substrates have physiological and pharmacological relevance. They may also have significant value as targets in modulating gene expression in the innate immune system and inflammatory response (912).…”
Section: Introductionmentioning
confidence: 99%
“…PEPT1 is expressed predominantly in the intestine and mediates the absorption of dietary nutrients (di/tripeptide) or peptidomimetic drugs ( 8 ). As PEPT1 is able to transport a broad spectrum of substrates, it is an attractive target for drug delivery ( 9 ). Previous studies on the presence and function of PEPT1 in carcinomas was limited in a number of carcinoma cell lines, including colon carcinoma Caco-2 cells ( 10 ), pancreatic carcinoma cell lines AsPc-1 and Capan-29 ( 11 ), gastric cancer ( 12 ), prostate cancer ( 13 , 14 ) and fibroblast-derived tumor cells ( 15 ), which indicates that PEPT1 may be expressed in other types of cancer cells.…”
Section: Introductionmentioning
confidence: 99%